2014
DOI: 10.1007/s12032-014-0977-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher miR-21 expression in invasive breast carcinomas is associated with positive estrogen and progesterone receptor status in patients from Serbia

Abstract: MicroRNAs play essential role in breast carcinoma progression and invasion. Our principal goals were to assess clinicopathological and prognostic correlations of microRNA-21 (miR-21) expression levels in a group of 39 Serbian breast cancer patients with invasive lobular (ILC), ductal (IDC), or mixed (ILC-IDC) breast carcinomas and in order to discover the role of miR-21 in potential novel form of stratification of the patients with different estrogen receptor (ER) and progesterone receptor (PR) status. MiR-21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 31 publications
3
5
0
Order By: Relevance
“…In fact, it was described that miR-21 is involved in positive hormonal breast carcinoma especially in those expressing HER2 that upregulate miR-21 and, therefore, it is involved in positive hormonal breast cancer subtypes since it appeared to interact with the α ER pathway [33], [34], [35]. However, according to our results, we found that this microRNA is more expressed in the negative hormonal receptors among the Tunisian population.…”
Section: Discussionsupporting
confidence: 48%
“…In fact, it was described that miR-21 is involved in positive hormonal breast carcinoma especially in those expressing HER2 that upregulate miR-21 and, therefore, it is involved in positive hormonal breast cancer subtypes since it appeared to interact with the α ER pathway [33], [34], [35]. However, according to our results, we found that this microRNA is more expressed in the negative hormonal receptors among the Tunisian population.…”
Section: Discussionsupporting
confidence: 48%
“…Indeed, the development of targeted therapeutics to upregulate these particular tumor suppressor miRNAs may serve as a promising strategy to treat ER + breast cancer. In contrast, several oncomiRs have consistently been reported to be upregulated in ER + breast cancer, such as miR-10b and miR-21 [ 4 6 ]. In particular, the tumor suppressor PTEN , which dephosphorylates PIP 3 and in turn blocks PI3K/Akt signaling, is a direct target of many oncomiRs that are overexpressed in ER + breast cancer (Table 1 ).…”
Section: Mirnas Associated With Er + Versus Er mentioning
confidence: 99%
“…invasion and migration, as well as TGF-β-mediated invasion and migration in breast cancer cells and these effects were due to miR-21-induced downregulation of smad7. miR-21 is expressed at high levels in cancer cells in invasive breast cancers (35) and findings of previous studies (including our previous study) have shown that miR-21 plays an important role in breast cancer metastasis (36)(37)(38). In the present study, miR-21 was overexpressed in the plasma of patients with breast cancer, demonstrating that miR-21 plays an important role in cancer cell invasion and migration, as metastasis, indicating that plasma miR-21 levels may serve as a diagnostic marker in breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, miR-21 facilitated deleterious cross-talk between EGF and TGF-β in a manner that promotes breast cancer cell invasion and migration. Given that miR-21, EGFR and TGF-β are often overexpressed in breast cancers (12,18,20,26,35,39), these observations suggest that suppression of miR-21 may prevent invasion and possibly metastasis in breast cancers, while interrupting deleterious EGF-TGF-β interactions that have the potential to contribute to breast cancer cell proliferation in vivo.…”
Section: Discussionmentioning
confidence: 99%